Targeting B cells to modify MS, NMOSD, and MOGAD: Part 2. Issue 1 (January 2021) - Graf, Jonas; Mares, Jan; Barnett, Michael; Aktas, Orhan; Albrecht, Philipp; Zamvil, Scott S.; Hartung, Hans-Peter
Abstract : Ocrelizumab, rituximab, ofatumumab, ublituximab, inebilizumab, and evobrutinib are immunotherapies that target various B cell–related proteins. Most of these treatments have proven efficacy in relapsing and progressive forms of MS and neuromyelitis optica spectrum disease (NMOSD) or are in advanced stages of clinical development. Currently, ocrelizumab and inebilizumab are licensed for treatment of MS and NMOSD, respectively. This part of the review focuses on monoclonal antibody B cell–depleting strategies in NMOSD and the emerging related myelin oligodendrocyte glycoprotein (MOG) immunoglobulin G–associated disease (MOGAD). Case series and phase 2/3 studies in these inflammatory disorders are assessed. The safety profile of long-term B-cell depletion in MS, NMOSD, and MOGAD will be highlighted. Finally implications of the current coronavirus disease 2019 pandemic on the management of patients with these disorders and the use of B cell–depleting agents will be discussed.